Six Decades of Research, Teaching, and Participation in the AAA - Beaver, William H. (The Accounting Review, 2015)
ABSTRACT These remarks provide some perspective on my six decades of research, teaching, and participation in the AAA. A recurring theme is that my career took several unexpected turns and that my research often had unexpected outcomes. Several areas of research are discussed, including the prediction of financial distress, the information content of earnings announcements, the information content of prices, accounting and market measures of risk, discretion in financial reporting, conservatism, and value relevance of financial statements. Included is a brief summary of some of what I have learned from six decades of teaching. I review some of the major benefits of AAA participation.